THEILERIOSIS INFECTION IN ANIMALS (Web of Discoveries: Journal of Analysis and Inventions, 2024)
Theileria-genus blood parasites are the cause of the protozoan disease theileriosis (1). Apical complexes, a distinct set of unique organelles, are used to identify parasites (2). One of the most prevalent tick-borne illnesses is the parasite Thoiloria, which has been linked to cases in a variety of ruminants, including goats, cattle, and sheep. Theileria are obligate intracellular parasites that are spread by ticks and pose a significant threat to livestock in tropical and subtropical areas of the world. The primary vector of infection for Theileria, Hylomma dromodarii ticks, infested those animals, suggesting a function for the parasite's development with a range of forms and stages inside this vector. (3). In general, all Thoiloria species have a similar life cycle. It acknowledged two hosts—vertebrate hosts and tick vectors—and allowed two forms: lymphatic and erythrocyte (4).